PENGARUH KEPEMIMPINAN DAN KESELAMATAN KESEHATAN KERJA (K3) TERHADAP KINERJA KARYAWAN - ASEP KURNIAWAN; SUKRISPIYANTO (AKADEMIKA, 2020)
The purpose of this study was to determine and analyze whether leadership and occupational health safety (K3) have a partially significant effect on employee performance at PT Pertamina Patra Niaga VHS Dipo Lok Malang, and also to determine which variables have dominant influence on employee performance at PT Pertamina Patra. Niaga VHS Dipo Lok Malang. The data analysis method used in this study is multiple linear regression analysis. Based on the method applied, it can be seen that the leadership factor has a partially significant effect on employee performance while the occupational health safety (K3) factor does not have a partial significant effect on employee performance. In addition, the leadership and occupational health safety (K3) factors simultaneously have a significant effect on employee performance. So it can be concluded that the leadership factor has a more dominant effect on employee performance because it has a partially and simultaneously significant effect than the occupational health safety (K3) factor which only has a simultaneous significant effect on employee performance.